PERTUMBUHAN TIGA SPESIES JANGKRIK LOKAL YANG DIBudidaya KAN PADA PADAT PENEBARAN DAN JENIS PAKAN BERBEDA - Priyantini Widiyaningrum (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
In the development of cricket farming, important information in regard with cultivated method, type of crickets, feedstuff, density level, and it’s productivity is essential. The aim of this study was to evaluate the effects of different density level and rations on growth performace of three species of local crickets, i.e Gryllus bimaculatus De Geer, Gryllus mitratus Burn and Gryllus testaceus Walk. Three levels of box square density (500, 750 and 1000 cricket/box) and two levels of additional feed (mustard green and papaya leaves)were used as treatments. The results showed that the density level of approximately 1000 cricket/box had no significant influence on growth performance of the three species local crickets. Nevertheless, higher density level tended to increase mortality rate especially for G. bimaculatus (rate of mortality = 45.86%). The use of feed combination of formulated ration plus mustard green resulted in better growth performance and higher egg production compared to the combination of formulated ration plus papaya leaves.